Infertility treatment via In -vitro fertilization: a Juristic analysis of unwanted embryo destruction - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (University of Chitral, 2019)
In Vitro Fertilization (IVF) has emerged as one of the most popular byproduct of Assistant Reproductive Technology (ART) in our time. It has proven attractive to people across the globe for variety of reasons including infertility treatment and pre-natal sex selection. People of various cultures have reacted to its use in line with their own code of morality and religious values on human procreation, sexual purity and lineage exactitude. In the case of Muslims, its application in the overcoming infertility has received general juridical approval with minim number of caveats. A cursory of the existing fatwas, however reveals that the juristic deliberation on the implications of IVF in terms of destroying the excess embryos generated in the process is scanty. Accordingly, this study argues that if we equate legitimate use of IVF with natural way of human reproduction, then the ethicality of its casualties in terms of surplus embryo destruction should not be trivialized.